Analysis of geometrical features of e-shaped core Μ-coil fluxgate magnetometer - Mohammed Thameemul Ansari , M. H.; Sulaiman, Nadzril; Jusoh, Ahmad Zamani (Asian Research Publishing Network (ARPN), 2015)
This paper presents the variation analysis of micro-coil fluxgate magnetometer. The design and analysis have been carried out using COMSOL multiphysics. The performance of the μ-coil have been analyzed by taking three different combinations of one parameter into account such as number of turns in order to find the optimized design. The optimized design of the micro coil can be used as a reference for the future fabrication of μ-scale fluxgate magnetometer. According to the results we found that the optimized design which has more number of turns. Therefore the number of turns has been adjusted to finalize the sensitive device. Hence, the coil with more number of turns has more sensitivity than the other with 0.053 mV.